Defatted black soldier fly larvae meal as a substitute of soybean meal in dairy cow diets - Braamhaar, D.J.M.; Pellikaan, W.F.; List, D.; Korir, Daniel; Tanga, C.M.; Oosting, S.J. (Elsevier, 2025)
The replacement of soybean meal (SBM) with insect meal, e.g. black soldier fly larvae meal (BSFLM), as an alternative protein source in livestock feed is gaining traction globally. To date, no in vivo studies have been conducted to test the impact of BSFLM on the milk production of dairy cows. This study quantified the effects of replacing SBM with defatted black soldier fly larvae meal (DBSFLM) in diets of lactating dairy cows on feed intake, milk production and composition, apparent total-tract digestibility, feed- and nitrogen use efficiency. Twelve lactating Holstein-Friesian cows were used in a replicated 3 × 3 Latin square design (18 d per period) with 3 protein treatments: a diet containing SBM as the main protein source (control, SBM); a diet with a 50: 50 mixture of SBM and DBSFLM (SBM: DBSFLM, 50: 50); and a diet with DBSFLM (DBSFLM). Animals were blocked per Latin square based on milk yield (MY), and the amount of concentrate in the diets was adjusted for MY. Diets were provided as a total mixed ration and offered ad libitum. Our results showed no treatment effects (P > 0.05) on milk yield and composition. DM and organic matter (OM) intake were significantly higher (P ≤ 0.003) for cows fed SBM (17.6 and 16.2 kg/d, respectively) compared with DBSFLM (16.6 and 15.1 kg/d, respectively), while DM and OM intake of SBM: DBSFLM (17.5 and 16.0 kg/d, respectively) did not differ from SBM but were higher compared with DBSFLM. CP intake was significantly higher (P = 0.003) for cows fed SBM (2.68 kg/d) compared with both DBSFLM (2.50 kg/d) and SBM: DBSFLM (2.54 kg/d), while CP intake for SBM: DBSFLM did not differ from DBSFLM. Apparent total-tract digestibility of NDF and ADF were significantly lower (P ≤ 0.024) for cows fed SBM (46.7 and 45.6%, respectively) compared with DBSFLM (54.0 and 52.0%, respectively), with SBM: DBSFLM (51.0 and 49.7%, respectively) not differing from either diet. No treatment effects were observed for DM, OM, CP and ether extract digestibility, and feed and nitrogen use efficiency. Incorporating DBSFLM into dairy cow diets did not significantly compromise the milk yield and composition, suggesting its potential to reduce the reliance on SBM and contribute to circular food systems.